O1: DISCOVERING NOVEL THERAPEUTICS TO TREAT ACUTE TRAUMATIC COAGULOPATHY (ATC). (27th April 2021) - Thaventhiran, A; Thiemermann, C; Brohi, K; Tremoleda, JL; Davenport, RA
Abstract: Introduction: In the UK, 17, 000 people die from injury each year, with uncontrolled bleeding the most significant cause of preventable mortality. Acute Traumatic Coagulopathy (ATC) exacerbates bleeding through the failure of blood‐clotting with accelerated clot breakdown that mechanistically is driven by activated Protein C (aPC). No targeted therapy to treat the underlying cause of ATC exists with treatment limited to blood component resuscitation and antifibrinolytic drugs to prevent premature clot breakdown. Method: Two hundred fifty‐four bleeding trauma patients had Factor V and aPC measured on arrival and during resuscitation. A preclinical ATC model was used to test the novel therapeutic recombinant Factor V (rFV), which is resistant to aPC mediated cleavage. Mice underwent combined injury and pressure controlled‐blood loss with intervention at 30‐minutes to represent a clinically relevant model. Coagulopathy was measured by ROTEM and biomarkers of coagulation/fibrinolysis. Result: Admission levels of FV were 38% lower (83 vs 134u/dL, p<0.0001), deteriorated during resuscitation to 65% of normal after transfusion of eight RBC units and were inversely related to aPC levels. Compared to vehicle, animals treated with rFV had reduced coagulopathy (Clot Strength at 5 minutes: 31 vs 24mm,  p<0.01) and significantly improved survival (80% vs 44%,  p≤ 0.001). Conclusion: FV falls significantly during bleeding in trauma patients and in the murine model, rFV improved coagulation suggesting it may represent a potential therapeutic target for ATC. Take‐home message: Directly targeting the cause of ATC represents a novel therapeutic strategy in trauma and may improve survival after major haemorrhage by directly improving clot function.